Enlivening vast green spaces of Zamość. Spatial organization of key recreational areas of the Town. Planty - Kielin, Katarzyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Today’s city longs for air and green. Congestion, overflow of car traffic, the pace and randomness of contemporary living might serve as plights for the spaces around us since one might observe accruing amounts of waste produced by humans, pollution or disorganization/ inconsistency/ incongruity of public spaces. Quite threatening might that be, but there has been observed a ‘trickling’, continuous shift of a social life towards virtual reality of tempting, alluring social media, games, news on-and-on broadcasts, shopping websites. We engage in perversely intimate relation with our ‘cuddle-to’ electronic devices – phones, laptops, smartphones. Little Prince would not be happy with ‘our establishing ties’ with lifeless machines, would he? Getting children out of their computers to kick some ball or play hide-and-seek turns into changing the current of a river or tempering with a bee. It will definitely stab you. Can a historically charged, conservatory space be a no space?